Kepemimpinan Transformasional Pengasuh dan Budaya Organisasi Pondok Pesantren: Tinjauan Sistematik Literatur - Gunadi, Ikhsan; Asriana Kibtiyah; Andhika Putra Widyadharma (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2026)
The leadership of the kiai (Islamic boarding school leader) is a central element in sustaining and developing pesantren as Islamic educational institutions with distinctive social, religious, and cultural characteristics. This study aims to explore the relationship between the transformational leadership of the kiai and the formation of organizational culture in pesantren through a systematic literature review (SLR) approach. The study analyzes relevant scholarly articles on pesantren leadership, transformational leadership in Islamic education, and pesantren organizational culture through stages of identification, selection, data extraction, and synthesis. The findings indicate that the transformational leadership of the kiai plays a strategic role in shaping an organizational culture grounded in Islamic values, such as moral exemplarity, discipline, scholarly tradition, and devotion (khidmah). The kiai functions not only as a structural authority but also as a source of moral and spiritual legitimacy that shapes social interactions and collective values within the pesantren. Furthermore, transformational leadership practices in pesantren exhibit unique characteristics distinct from modern organizational models, particularly in integrating spiritual authority, moral exemplarity, and community empowerment. This study proposes a conceptual model of pesantren transformational leadership that emphasizes spiritual charisma, transformative educational vision, exemplary leadership, and community empowerment as the foundation for developing a value-based organizational culture.